Lodging in wheat: genetic and environmental factors and ways of overcoming - E. V. Ageeva; I. N. Leonova; I. E. Likhenko (Вавиловский журнал генетики и селекции)
Lodging is one of the main factors in reducing the yield and grain quality of winter and spring wheat varieties. The resistance of wheat cultivars to lodging largely depends on environmental factors, biological and morphological features of the stem and root systems. Selection of the varieties for resistance to lodging is relevant in many countries of the world and has a number of achievements. Plant height is one of the most important morphological characters associated with lodging resistance. Breeding of the varieties carrying the dwarfing genes (Rht) is the main direction to reduce the risk of lodging. The Rht-B1b, Rht-D1b, Rht8 and Rht11 genes are widely used throughout the world due to their significant influence on agronomically valuable traits, including lodging. It turned out to be important to study the anatomical and morphological features and chemical composition of stem tissues, which complement the assessment of resistance to lodging and allow the varietal material to be more fully characterized. The thickness of stem internodes and their anatomical structure play an important role in the stem strength. The diameter of the stem, its thickness and weight, a large number of vascular bundles and a wide ring of mechanical tissues correlate with resistance to lodging. The content of lignin, silicon and cellulose are important structural components and provide the stem strength of wheat plants. Molecular genetic analysis and mapping of genes and quantitative trait loci are of great importance in identifying the genetic basis of the relationship between the anatomical and morphophysiological characters of the stem and root system and lodging. Genetic factors reflecting correlations between the lodging and the thickness of the stem wall, the number of vascular bundles and other characters were mapped to chromosomes 1A, 1B, 2A, 2D, 3A, 4B, 4D, 5A, 5D, 6D and 7D. It has been found that loci with high phenotypic effects on lodging tolerance are colocalized with loci responsible for plant height, stem diameter and stem strength. To increase resistance to lodging, it is necessary to develop a set of agrotechnical methods that reduce the influence of soil and climatic factors and create wheat varieties tolerant to lodging.